2014
DOI: 10.1148/rg.346130089
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Imaging for Characterization, Classification, and Staging of Malignant Pleural Mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is the most common primary malignancy of the pleura and is associated with asbestos exposure in approximately 80% of patients. The patient prognosis is poor, with a median survival of 9-17 months after diagnosis. However, improved survival and decreased morbidity and mortality have been demonstrated when the diagnosis is made in the early stages of disease and specific treatment strategies are implemented. A staging system that focuses on the extent of primary tumor (T), ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 45 publications
0
83
2
1
Order By: Relevance
“…Malignant pleural mesothelioma may involve the diaphragm, and trans-diaphragmatic extension may be detected on CT examination (15). A rind-like pleura, with a thickness of >10 mm is crucial for the diagnosis of malignant pleural mesothelioma (16).…”
Section: Discussionmentioning
confidence: 99%
“…Malignant pleural mesothelioma may involve the diaphragm, and trans-diaphragmatic extension may be detected on CT examination (15). A rind-like pleura, with a thickness of >10 mm is crucial for the diagnosis of malignant pleural mesothelioma (16).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, approximately 20-30% of patients undergoing thoracoscopy for MPM are found to be suitable candidates for resection due to discrepancy between preoperative radiological and operative findings [11,12,13,14]. More recently, several studies aimed to define the role of PET/CT in pretherapeutic MPM staging and showed good accuracy for mediastinal lymph nodes assessment as well as extra thoracic metastases, but with comparatively poor evaluation of the pleural cavity [15,16,17,18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…A A B C D recent review of diagnostic performance of CT reported a sensitivity and specificity of 68% and 78%, respectively, for pleural malignancy (21). CT cannot differentiate MPM from metastatic pleural malignancy, although circumferential pleural thickening and mediastinal pleural involvement are more frequent in MPM.…”
Section: Ct Scanmentioning
confidence: 99%